Information and communication technologies for ageing well and e-Health : first International Conference, ICT4AgeingWell 2015, Lisbon, Portugal, May 20-22, 2015. Revised selected papers /: first International Conference, ICT4AgeingWell 2015, Lisbon, Portugal, May 20-22, 2015. Revised selected papers. (2015) - Unknown
No abstract available